Use of Single-Item Self-Rated Health Measure to Identify Frailty and Geriatric Assessment-Identified Impairments Among Older Adults with Cancer. (28th January 2022) - Giri, Smith; Mir, Nabiel; Al-Obaidi, Mustafa; Clark, Deanna; Kenzik, Kelly M; McDonald, Andrew; Young-Smith, Crystal; Paluri, Ravi; Nandagopal, Lakshmin; Gbolahan, Olumide; Nyrop, Kirsten A; Muss, Hyman B; et al.
Abstract: Background: Poor self-rated health (SRH) is a known predictor of frailty and mortality in the general population; however, its role among older adults with cancer is unknown. We evaluated the role of SRH as a potential screening tool to identify frailty and geriatric assessment (GA)-identified impairments. Materials and Methods: Adults ≥60 years diagnosed with cancer in the UAB C ancer & A ging R esilience E valuation (CARE) registry underwent a GA at the time of initial consultation. We measured SRH using a single-item from the Patient-Reported Outcomes Measurement Information System global health scale and dichotomized responses as poor (poor, fair) and good (good, very good, and excellent). We evaluated the diagnostic performance of SRH in measuring frailty, and GA impairment (≥2 deficits among a set of seven GA domains). We examined the impact of SRH with survival using a Cox model adjusting for confounders, exploring the mediating role of frailty. Results: Six hundred and three older adults with cancer were included, with a median age of 69 years. Overall, 45% ( n = 274) reported poor SRH. Poor SRH demonstrated high sensitivity and specificity for identifying frailty (85% and 78%, respectively) and GA impairment (75% and 78%, respectively). In a Cox regression model, poor SRH was associated with inferior survival (HR = 2.26; 95% CI 1.60-3.18) after adjusting for confounders; frailty mediated 69% of this observed relationship. Conclusion: Self-rated health may be used as a screening tool to identify older adults with cancer with frailty and GA impairments. Poor SRH is associated with inferior survival, which is mediated by frailty. Abstract : This article evaluates the role of self-rated health as a potential screening tool to identify frailty and geriatric assessment-identified impairments.